Mg/Ca ratios in the planktonic foraminifer Neogloboquadrina pachyderma (sinistral) in the northern North Atlantic/Nordic Seas - Meland, My; Jansen, E; Elderfield, H; Dokken, Tm; Olsen, A; Bellerby, Rgj (Geochemistry, Geophysics, Geosystems, 2006)
In core top samples in the Nordic Seas, Mg/Ca ratios of N. pachyderma ( sin.) are generally consistent with previous high-latitude calibration data but do not reflect the modern calcification temperature gradient from 2 degrees C in the northwest to 8 degrees C in the southeast. This is because Mg/Ca ratios in foraminiferal shells from the central Nordic Seas are similar to 0.4 mmol/mol higher than expected from calibrations of Nurnberg ( 1995) and Elderfield and Ganssen ( 2000). The enhanced Mg/Ca ratios are observed in an area with low sedimentation rates (< similar to 5 cm/kyr). Possible factors that may cause this include bioturbation, Holocene variability in old core tops, dissolution, pore water chemistry, occurrence of volcanic ash, and other natural variability. The enhanced foraminiferal Mg/Ca ratios in areas of the Nordic Seas and the northern North Atlantic may also be linked with secondary factors related to the presence of fresher and colder water masses, possibly combined with pore water chemistry in low-sedimentation areas differing from high-sedimentation areas.